POTENSI HIDROLISAT PROTEIN IKAN DALAM KONTROL GLUKOSA DARAH DAN NAFSU MAKAN PADA OBESITAS UNTUK MENCEGAH DIABETES MELITUS TIPE 2: LITERATURE REVIEW - Herlina Hapsari; Etika Ratna Noer; Fitriyono Ayustaningwarno (Journal of Nutrition College, 2026)
ABSTRACTBackground: Obesity is a metabolic disorder and one of the most critical human health issues worldwide. It can lead to an increased risk of metabolic diseases, such as diabetes mellitus and cardiovascular diseases. Fish protein hydrolysate (FPH) has been recognized as a potential source of bioactive peptides that may aid in regulating blood glucose homeostasis and appetite management in obese individuals, hence potentially decreasing the risk of developing type 2 diabetes mellitus.Objective: To explore the effects of fish protein hydrolysate (FPH) on blood glucose control and appetite regulation, and to analyze its impact on weight loss in obese individuals to prevent type 2 diabetes mellitus.Methods: A literature review of five databases: PubMed, Science Direct, Scopus, Cochrane Library, and Google Scholar. The keywords related to type 2 diabetes mellitus, blood glucose, fish protein hydrolysate, obesity, bioactive peptides and satiety with inclusion criteria of articles in English published in the last decade (2015–2025). Results: Through disruptions in insulin sensitivity and satiety signals, glucose dysfunction and appetite dysregulation in obese individuals significantly contribute to an increased risk of type 2 diabetes mellitus. The mechanism of action of fish protein hydrolysate (HPI) has been shown to help regulate appetite and glucose homeostasis by stimulating satiety hormones such as GLP-1 and increasing the availability of certain amino acids responsible for energy metabolism.Conclusion: HPI may influence reductions in weight loss and the regulation of certain metabolic biomarkers, particularly in individuals with overweight or metabolic syndrome. However, the reported information on how HPI affects appetite regulation, digestive hormone secretion, and blood glucose control remains varied and not fully consistent.Keywords: Type 2 diabetes mellitus; blood glucose; fish protein hydrolysate; obesity; satiety ABSTRAKLatar belakang : Obesitas adalah gangguan metabolisme dan salah satu masalah manusia yang paling kritis di seluruh dunia. Hal ini dapat menyebabkan risiko penyakit metabolik, seperti diabetes melitus tipe 2 (DM tipe 2) dan penyakit kardiovaskular. Hidrolisat Protein Ikan (HPI) telah muncul sebagai komponen bioaktif peptida yang berpotensi dengan keuntungan potensial membantu kontrol glukosa darah dan nafsu makan  pada obesitas dan mencegah terjadinya diabetes melitus tipe 2.Tujuan: Mengeksplorasi efek hidrolisat protein ikan (HPI) pada kontrol gula darah dan regulasi nafsu makan serta menganalisis dampaknya dalam menurunkan berat badan pada penderita obesitas untuk mencegah diabetes melitus tipe 2.Metode: Tinjauan pustaka terhadap lima database: PubMed, Science Direct, Scopus, Cochrane Library dan Google Scholar. Kata kunci yang terkait dengan diabetes mellitus tipe 2, glukosa darah, hidrolisat protein ikan, obesitas, peptida bioaktif dan rasa kenyang, dengan kriteria inklusi artikel dalam bahasa Inggris yang diterbitkan dalam satu dekade terakhir (2015–2025). Hasil: Melalui gangguan pada sensitivitas insulin dan sinyal kenyang, disfungsi glukosa dan disregulasi nafsu makan pada orang obesitas berkontribusi secara signifikan terhadap peningkatan risiko DM tipe 2. Mekanisme kerja hidrolisat protein ikan (HPI) terbukti dapat membantu mengatur nafsu makan dan homeostasis glukosa dengan menstimulasi hormon kenyang seperti GLP-1 dan meningkatkan ketersediaan asam amino tertentu yang bertanggung jawab atas metabolisme energi.Simpulan: HPI dapat mempengaruhi penurunan berat badan dan pengaturan biomarker metabolik tertentu, terutama pada orang dengan kelebihan berat badan atau sindrom metabolik. Namun, informasi yang dilaporkan tentang bagaimana HPI mempengaruhi regulasi nafsu makan, sekresi hormon pencernaan, dan kontrol glukosa darah masih beragam dan belum sepenuhnya konsisten.Kata Kunci : Diabetes melitus tipe 2; glukosa darah; hidrolisat protein ikan; obesitas, rasa kenyang